2015
DOI: 10.5539/ijef.v7n2p78
|View full text |Cite
|
Sign up to set email alerts
|

Family Ownership, Corporate Governance and Performance: Evidence from Saudi Arabia

Abstract: The main objective of this study is to examine the performance of companies listed in the Saudi Stock Exchange. For this purpose, we studied and tested a sample of 792 firm-years among from 11 industrial groups for the years 2006 to 2013 and compared Family and Non-family firms. The research addresses the questions 1) Do family owned firms perform better? 2) How does concentration of ownership affect firm performance, comparing family firms to non-family ones? This research attempts to fill a research gap on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 47 publications
5
41
0
5
Order By: Relevance
“…Thus, hypothesis H1 is supported. This finding is consistent with previous studies that found a positive relationship between family ownership and firm performance such as [17]. As for the hypothesis H2, the finding is consistent with [28] and [29], that found a positive relationship between foreign ownership and firm performance.…”
Section: Regression Results Of Model (Based On Accounting Measure)supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, hypothesis H1 is supported. This finding is consistent with previous studies that found a positive relationship between family ownership and firm performance such as [17]. As for the hypothesis H2, the finding is consistent with [28] and [29], that found a positive relationship between foreign ownership and firm performance.…”
Section: Regression Results Of Model (Based On Accounting Measure)supporting
confidence: 92%
“…Islamic law in Jordan gives the right for a woman to keep the name of her father after marriage. Therefore, the names of second generation owners in family firms will be clear and easy to identify [17].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The results found that corporate governance and firm value (measured as Tobin's Q and market value of equity) are positively related. In line with this study Al-Ghamdi, and Rhodes, (2015) study the Family Ownership, Corporate Governance and Performance in Saudi listed companies on sample of 792 observations for the period from 2006 to 2013. The analysis shows that ownership has a significant positive relationship if measured by Tobin's Q.…”
Section: Corporate Governance and Financial Performancementioning
confidence: 93%
“…Karena salah satu tujuan utama dalam kegiatan bisnis untuk menghadapi persaingan global yang semakin ketat adalah bagaimana meningkatkan kinerja di suatu perusahaan (Al-Ghamdi dan Rhodes, 2015).…”
unclassified
“…Masalah keagenan muncul karena pemisahan antara fungsi kepemilikan dan pengelola perusahaan. Penelitian AlGhamdi dan Rhodes (2015) menunjukan bahwa konsentrasi kepemilikan memiliki pengaruh positif signifikan terhadap kinerja perusahaan. Hastori et al (2015) menyatakan dengan semakin terkonsentrasinya kepemilikan saham, maka pemilik saham yang besar dapat mempunyai insentif lebih untuk mengawasi kinerja para eksekutif, sehingga tindakan dan kebijakan para manajer yang tidak sejalan dengan tujuan perusahaan langsung dapat diketahui dan dicegah.…”
unclassified